Bacterial profile and patterns of antimicrobial drug resistance in intra-abdominal infections: Current experience in a teaching hospital - Neetu Shree; Balvinder S Arora; Ravinder S Mohil; Dimple Kasana; Indu Biswal (Wolters Kluwer Medknow Publications, 2013)
Context: Bacterial isolates from intra-abdominal infections, in particular, peritonitis and their unpredictable antimicrobial resistance patterns, continue to be a matter of concern not only globally but regionally too. Aim: An attempt in the present study was made to study the patterns of drug resistance in bacterial isolates, especially gram negative bacilli in intra-abdominal infections (IAI) in our hospital. Materials and Methods: From 100 cases of peritonitis, identification of isolates was done as per recommended methods. Antimicrobial susceptibility and extended-spectrum beta-lactamase (ESBL) testing were performed following the CLSI guidelines. Results: A total of 133 clinical isolates were obtained, of which 108 were aerobes and 22 anaerobes. Fungal isolates were recovered in only three cases. Escherichia coli (47/108) emerged as the most predominant pathogen followed by Klebsiella spp. (27/108), while Bacteroides fragilis emerged as the predominant anaerobe (12/22). Among coliforms, 61.7% E. coli and 74.1% Klebsiella spp. were ESBL positive. A high level of resistance was observed for beta lactams, ciprofloxacin, amikacin, and ertapenem. Ertapenem resistance (30-41%) seen in coliforms, appears as an important issue. Imipenem, tigecycline, and colistin were the most consistently active agents tested against ESBL producers. Conclusion: Drug resistance continues to be a major concern in isolates from intra-abdominal infections. Treatment with appropriate antibiotics preceded by antimicrobial resistance testing aided by early diagnosis, adequate surgical management, and knowledge of antibiotic - resistant organisms appears effective in reducing morbidity and mortality in IAI cases.